The Urgency of Independent Learning in Virtual Learning: Urgensi Kemandirian Belajar dalam Pembelajaran Virtual - Windi Diah Agustyani; Ida Rindaningsih (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this study was to determine the importance of independent learning in virtual learning. The protracted pandemic period makes students miss learning. Students must quickly adapt to technology and learn without a classroom. To overcome this, students are needed with independent learning in virtual classes using media that are adapted to the material presented by the teacher. This study uses quantitative research with a sample of 17 students in grade IV SD Muhammadiyah 1 Ngimbang . The results are obtained from the calculation of the questionnaire with a percentage of 94% of students answering 'YES', and the results of t-count with a price of tcount 0.150 > ttable 2.119, which means H1 is accepted and H0 is rejected. And the results of the influence of variables on the value of R Square are 0.255, which means that the virtual classroom learning media variable has an effect on student learning independence by 25.5%.